Rare case presentation of parathyroid adenoma in a young female presenting as pathological fracture of long bones: A case study - P Ajay Kale; Himanshi Vats (Indian Journal of Health Sciences and Biomedical Research KLEU, 2023)
Primary hyperparathyroidism (PHPT) is usually seen in females above the age of 50 years, with a prevalence of 21/1000 whereas the incidence in patients aged 12–28 years is <5%. A solitary adenoma is responsible for 80% of cases of PHPT. PHPT is most commonly asymptomatic. The young age of the patient and her presentation with osteoporosis and bone fractures make this an extremely rare presentation of parathyroid adenoma (PTA). Here, we report a case of PTA in a young female presented with pathological fracture of tibia and humerus. The case was diagnosed as PTA based on clinical symptoms and investigations. Surgical intervention, i.e. parathyroidectomy was performed under GA.